The Development of Using English Conjunction Skills in Contemporary Songs - อภิสุนทรางกูร, ปิยาพร (Journal of Roi Et Rajabhat University, 2016)
This research aimed to study the skill development among students in using English conjunctions in contemporary English language songs. The sample was 75 first-year Business English major students at Loei Rajabhat University, 11 males and 64 females. Pre-test and Post-test of the use of English conjunctions, which were approved by the three experts, and were distributed to the subjects at the beginning and the end of the course to collect the data. The data then were statistically analyzed with SPSS program to find out means, percentage, standard deviation and to conduct a t-test. The results from the pre-test of conjunctions revealed that the students scored 8.09 on average while the posttest score was 14.57 on average. The average scores of post-test was higher and it was also found that the Sig. (2tailed) at < .0001. These could interpret that the skill development in using English conjunctions in contemporary songs was effective for the learners with statistically significant at the 0.05 level. Moreover, the study on the survey of students' satisfaction showed that they satisfied at the ratio of 4.10.